Genetic Diagnosis of Familial Hypercholesterolaemia: The Importance of an Integrated Analysis of Clinical, Molecular and Functional Data - Alves, A.C. (2016)
Familial Hypercholesterolaemia (FH) is one of the most common monogenic disorders, being caused mostly by mutations in LDL receptor (LDLR) gene. The high levels of LDL cholesterol presented since birth confers these patients an increased cardiovascular risk. Laboratory techniques have improved greatly recently and new variants are found every day that need to be validated as mutations causing disease for the correct diagnosis of FH. The aim of this study was to characterize both at the phenotypic and genotypic level, families with a clinical diagnosis of FH and discuss the importance of the integration of clinical, molecular and functional data for the correct diagnosis of these patients.